Nursing care in a vulvar cancer patient - Hernández-Estrada, Karen Melissa (Universidad de Sonora, 2019)
Introduction: The squamous cell carcinoma or squamous cells is common on organs lined by squamous epithelium such as the skin, vagina, and cervix. Nursing personnel have a critical role in the treatment of the person with this illness, inorder to improve their quality of life during and after the illness treatment. Objective: Present the nursing care provided to a patient with vulvar cancer during the oncology consultation in a public hospital in the city of Monterrey, Nuevo León, México, during 6 months. Methodology: Case study based on the five stages of the nursing care process. The taxonomy of the North American Nursing Diagnosis Association (NANDA), Nursing Intervention Classification (NIC), and Nursing Outcomes Classification (NOC) were used to substantiate the nursing interventions carried out. Case presentation: As a result of the assessment, the following was get as priority nursing diagnosis: acute pain, constipation, nausea, ignorance of treatment, and grieving due to the loss of a loved one. Applied interventions were: Pain management, spiritual support, education about the illness, and management of side effects of chemotherapy and radiotherapy. Conclusions: The patient developed non-pharmacological strategies to manage pain, which helped to control it, increased knowledge about the illness and treatment effects, which favored the management of secondary effects of the radiation and chemotherapy, and coped with the grief due to the loss of the loved one.